ANALISIS DENSITAS STOMATA TANAMAN ANTANAN (Centella asiatica, L) DENGAN PERBEDAAN INTENSITAS CAHAYA - Laurencius Sihotang (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2017)
This study aims to determine the effect of light intensity on stomatal density and shade effect on the formation of plant stomata antanan. This study using 60 samples with two treatments of 30 samples from places with shade and 30 samples from places without shade. The method used to observe the stomata in the leaf surface is a replica method of transparent nail polish. The parameters observed in this study is the density of stomata. A data were analyzed using SPSS 21 using t-test, to determine the effect of light intensity on stomatal density antanan plants. Statistical tests showed that there is a real difference between the density of stomata on the leaves of plants antanan in places without shade and the shade on the level of 5% ie t = 10.848> table = 2.045. It can be concluded that the intensity of sunlight due to shading greatly affect the formation and density of stomata on the leaves of plants antanan.Key word: Stomata, Antanan, Density, Intensity.